Expanded uncertainty assessment in fish samples analyzed by INAA and AAS (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Measurement uncertainty was estimated following the EURACHEM guide (Quantifying Uncertainty in Analytical Measurement) for the elements As, Br, Cl, Co, Cr, Cs, Fe, K, Mg, Mn, Na, Rb, Sb, Se and Zn determined by Instrumental Neutron Activation Analysis (INAA) and for the elements Cd, Hg and Pb determined by Atomic Absorption Spectrometry (AAS) in the fillet of the most consumed fish species at São Paulo city, Brazil. INAA expanded uncertainties ranged from 1.0 to 21% and the main contributions were due the counting statistics of sample and pipetted standards. For AAS, expanded uncertainties ranged from 6.5 to 13% and the main contributions were associated to the calibration curves. Uncertainty results were compared with the standard deviations of the mass fraction in the fishes (n = 10). Due to the wide variability in the mass fraction in the analyzed fish tissues, explained by factors such gender, age, fat content and fishing location of the specimens of each species, standard deviations were greater than expanded uncertainties, which means that the natural variability of the elements determined is greater than the data dispersion associated with the analytical techniques. Hence the used techniques were adequate for the fish fillet samples analyses.